Case Report: Persistent Hypogammaglobulinemia More Than 10 Years After Rituximab Given Post-HSCT - Luterbacher, Fanny; Bernard, Fanette; Baleydier, Frédéric; Ranza, Emmanuelle; Jandus, Peter; Blanchard-Rohner, Geraldine (Frontiers in Immunology, 2021)
Rituximab (RTX) is an anti-CD20 monoclonal antibody that targets B cells from the immature pre–B-cell stage in the bone marrow to mature circulating B cells, while preserving stem cells and plasma cells. It is used to treat autoimmune diseases, hematologic malignancies or post-hematopoietic stem cell transplantation (HSCT) complications. The safety profile is acceptable. However a subset of patients can develop a persistent hypogammaglobulinemia that can be associated with severe complications, especially in the pediatric population. We report the case of two unrelated young men of 17 and 22 years, who present persisting hypogammaglobulinemia respectively more than 7 and 10 years following treatment of RTX, administered post-HSCT for hemolytic anemia and Ebstein Barr Virus reactivation, respectively. An immunological workup in both patients showed decreased total immunoglobulin levels, vaccine antibodies and class-switched memory B cells, with increased in naive B-cells, which can also be observed in primary immunodeficiencies such as those corresponding to common variable immunodeficiency (CVID). Whole exome sequencing in one of the two patients could not detect a pathogenic variant causative of a mendelian immunological disorder. An annual assessment with interruption of immunoglobulin replacement therapy during summer period failed to demonstrate recovery of endogenous immunoglobulin production and of normal number of switched memory B cells 10 years and 7 years, respectively, after treatment with RTX. While the factors predisposing to a prolonged hypogammaglobulinemia post-rituximab remain unclear, if this treatment is necessary, a comprehensive immunologic workup before treatment and long-term follow-ups are mandatory in order to assess long-term complications, especially in children.